Gefitinib, an epidermal growth factor receptor blockade agent, shows additional or synergistic effects on the radiosensitivity of esophageal cancer cells in vitro - Taira, Naruto; Doihara, Hiroyoshi; Oota, Tetsuya; Hara, Fumikata; Shien, Tadahiko; Takahashi, Hirotoshi; Yoshitomi, Seiji; Ishibe, Youichi; Shimizu, Nobuyoshi (Acta medica Okayama, 2006)
Human esophageal cancers have been shown to express high levels of epidermal growth factor receptor (EGFR) and a relationship between high EGFR expression and local advance, the number of lymph node metastases, life expectancy, and sensitivity to chemo-radiotherapy has been demonstrated. We examined the use of gefitinib, an orally active EGFR-selective tyrosine kinase inhibitor, as a new strategy for treatment of esophageal carcinoma. The effects of gefitinib were evaluated in monotherapy and in combination with radiotherapy in human esophageal carcinoma cell lines. Gefitinib produced a dose-dependent inhibition of cellular proliferation in all of the 8 esophageal carcinoma cell lines examined, with IC50 values ranging from 5.7 microM to 36.9 microM. In combination, gefitinib and radiotherapy showed a synergistic effect in 2 human esophageal carcinoma cell lines and an additive effect in 5 cell lines. Western blotting demonstrated that gefitinib blocked activation of the EGFR-extracellular signal-regulated kinase (Erk) pathway and the EGFR-phosphoinositide-3 kinase (PI3K)-Akt pathway after irradiation. These results suggest that further evaluation of EGFR blockade as a treatment for esophageal cancer should be performed, and that radiotherapy combined with EGFR blockade may enhance the response of esophageal carcinoma to therapy.